At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
z=-3 so 2y+3(-3)=-8, 2y-9=-8, add 9 to both sides 2y=1 divide both sides by 2, y=1/2, so 3x+4(1/2)+-3=-2, 3x+2-3=-2, 3x-1=-2, add 1 to both sides, 3x=-1, divide both sides by 3, x=-1/3
Answer:
y = 1/2
x = -1 / 3
z = -3
Step-by-step explanation:
In this question, in order to find "y" and "x", we do the following...
Since we know z = -3 we can find "y" by substituting z in the second equation.
2y + 3z = -8
2y + 3(-3) = -8
2y - 9 = -8
2y = 1
y = 1/2
Now we know "y" and "z" and so we can find x...
3x + 4y + z = -2
3x + 4(1/2) - 3 = -2
3x + 2 - 3 = -2
3x = -1
x = -1 / 3
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.